Linear behavioral study of single storey house made from IBS engineering blocks under imperial valley, El_Centro 1940 earthquake - Mohd Asharuddin, Hassan (Universiti Malaysia Perlis (UniMAP), 2013)
Access is limited to UniMAP community.